A children retail company's e-commerce warehouse optimization - TUNABOYLU, BAHADIR (My University, 2022)
The efficient and well-designed warehouses can provide critical advantages for retail stores. They also play a crucial role in the achievement of supply chain management. Nowadays, warehouses have become centers where fast access to the customer is provided apart from the storage and protection of the goods. The objective of this study is to find the more efficient and useful warehouse design of A Children Retail Company, which is used for e-Commerce. The best place for the products will be determined by using a combination of such tools like the Pareto Principle, ABC Analysis, Technical Drawing, Simulation, and 5S Model. The optimum layout determined from the analyses enables more efficient work for warehouse employees, and orders to the logistics department are faster and more accurate for the facility. Moreover, an automation system is proposed with the barcode scanning and packaging part for the orders to simplify the existing complexity of the process.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; Endüstri Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; Industrial Engineering; Engineering and Technology; MÜHENDİSLİK, ENDÜSTRİYEL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); YÖNETİM; Ekonomi ve İş; Sosyal Bilimler (SOC); ENGINEERING, INDUSTRIAL; ENGINEERING; Engineering, Computing & Technology (ENG); MANAGEMENT; ECONOMICS & BUSINESS; Social Sciences (SOC); General Decision Sciences; Decision Sciences (miscellaneous); General Engineering; Engineering (miscellaneous); Social Sciences & Humanities; Physical Sciences; Supply chain; Warehouse; Optimization; e-Commerce; Layout; Automation; Supply chain; Warehouse; Optimization; e-Commerce; Layout; Automation